ASSESSING THE EFFECT OF COVID-19 ON LABORATORY PRACTICES: A REVIEW (The Research of Medical Science Review, 2025)
The COVID-19 pandemic significantly disrupted laboratory practices worldwide, necessitating rapid adaptations in diagnostic workflows, biosafety measures, staffing, and resource management. This study assesses the impact of COVID-19 on laboratory operations, focusing on changes in testing capacity, safety protocols, supply chain challenges, and workforce dynamics. The pandemic accelerated advancements in diagnostic technologies, automation, and digital transformation, while also highlighting vulnerabilities such as reagent shortages, increased workload, and mental health concerns among laboratory personnel. Additionally, disruptions to non-COVID testing and research activities raised concerns about long-term consequences on healthcare and scientific progress. This assessment provides insights into lessons learned, strategies for resilience, and recommendations for future pandemic preparedness to ensure laboratories remain efficient and sustainable in the face of global health crises. The COVID-19 pandemic is the most significant worldwide medical crisis of our time. Pakistan has poorer health care standards, an unstable economy, and little funding to combat the outbreak when compared to its neighbors China and Iran, who were identified as the pandemic's epicenters. Clinical laboratories face numerous difficulties, much like other organizations and sectors in the nation.